International environmental law - Dupuy, Pierre-Marie (University Press, 2015)
"This textbook provides a concise, conceptually clear, and legally rigorous introduction to contemporary international environmental law and practice. Written in an accessible style, the book covers all the major multilateral environmental agreements, paying particular attention to their underlying structure, their main legal provisions, and their practical operation. The material is structured into four sections: (I) Foundations, (II) Substantive regulation, (III) Implementation, and (IV) International environmental law as a perspective. The presentation of the material blends policy and legal analysis and makes extensive reference to the relevant treaties, instruments and jurisprudence. All chapters include a detailed bibliography along with numerous figures to summarise the main components of the regulation. It covers emerging topics such as foreign investment and the environment, environmental migration, climate change and human rights, technology diffusion, and environmental security in post-conflict settings"--